Pengaruh Pelatihan, Motivasi dan Disiplin terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervening - Anantha, Anggun; Wiratha, Andre; Adif, Riandy Mardhika (Jurnal Informatika Ekonomi Bisnis, 2025)
The main problem in the research is that in 2024 the performance of BPBD Tanah Datar Regency employees will decrease from the previous year. The motivation given to Tanah Datar Regency BPBD employees has not been maximized so that interest in improving performance is difficult to achieve. The role of job satisfaction as a mediating factor in the relationship between training, motivation and work discipline on employee performance has not been analyzed in depth, so its impact on improving performance has not been properly measured. The aim of the research is to explain the influence of training, motivation and discipline on employee performance with job satisfaction as an intervening variable at BPBD Tanah Datar. The type of research used was quantitative research with a field approach with a sample size of 36 employees at BPBD Tanah Datar Regency. The data analysis technique used in this study was path analysis. The results showed that training had a significant effect on employee performance, motivation had no significant effect on employee performance, discipline had a significant effect on employee performance, training had a significant effect on job satisfaction, motivation had a significant effect on job satisfaction, and discipline had a significant effect on job satisfaction. Job satisfaction mediated the effect of training on employee performance at the Tanah Datar Regency Regional Disaster Management Agency (BPBD), while job satisfaction did not mediate the effect of motivation on employee performance at the Tanah Datar Regency Regional Disaster Management Agency (BPBD), and job satisfaction mediated the effect of discipline on employee performance at the Tanah Datar Regency Regional Disaster Management Agency (BPBD).